PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP KEPERCAYAAN DIRI DAN HASIL BELAJAR MATA PELAJARAN MATEMATIKA KELAS III SD - Dhenok Agustin; Dadang Suhada; Wawan Setiawardani (STKIP Subang, 2025)
This study aims to the determine the significance of the influence of the role playing learning model on self confidence and learning outcomes of mathematics subjects in grade III of elementary school. This study uses a quasi experimental method with a nonequivalent control group design. This study used an experimental class and a control class with a total of 44 student. The experimental class uses a role playing learning model and the control class uses a lecture learning model. The instruments used in this study were questionnaires and tests. The data obtained were analyzed using SPSS version 22. The results of this study showed that the experimental class had an average (mean) of 67.63 while the control class had an average (mean) of 59.35, based on the results of the t-test obtained student self confidence showed a Sig. 0.000 < 0.05 furthermore, on the learning outcomes of students in the experimental class had an average (mean) of 84.00 while the control class had an average (mean) 0f 75.00, based on the results of the t-test obtained student learning outcomes showed a Sig. 0.000 < 0.05 this proves that the role playing learning model significantly influences the self confidence and learning outcomes of third grade student a public elementary school 1 Panunggul.